2014
DOI: 10.1166/sam.2014.1752
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Cytotoxicity Assessment of UV Absorbers-Intercalated Zinc/Aluminium-Layered Double Hydroxides on Dermal Fibroblast Cells

Abstract: Zn/Al-layered double hydroxide (LDH) was used as a host to intercalate various organic ultraviolet (UV) radiation absorbers. The intercalation compounds were prepared via the coprecipitation method. Powder X-ray diffraction (PXRD) confirmed the successful intercalation of anions into the interlayer regions of the LDH nanocomposites. As a result of intercalation, the resulting nanocomposites loaded with UV-ray absorbers, cinnamic acid (CA), benzophenone 4 (B4) and Eusolex®232 (EUS)-exhibited basal spacings of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Most importantly, a cytotoxic study revealed that all three nanocomposites were found to be biocompatible with HDF cells. 101 Mohsin et al have recently also developed a UV-absorbing nanohybrid (sunscreen formulation) by intercalating the strong UV absorber benzophenone-9 into Zn/Al LDHs. The sunscreen formulation was found to be stable in deionized water, artificial seawater, and in skin pH conditions.…”
Section: Layered Double Hydroxides In Uv Protection and Sunscreen Formentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, a cytotoxic study revealed that all three nanocomposites were found to be biocompatible with HDF cells. 101 Mohsin et al have recently also developed a UV-absorbing nanohybrid (sunscreen formulation) by intercalating the strong UV absorber benzophenone-9 into Zn/Al LDHs. The sunscreen formulation was found to be stable in deionized water, artificial seawater, and in skin pH conditions.…”
Section: Layered Double Hydroxides In Uv Protection and Sunscreen Formentioning
confidence: 99%
“…The cytotoxic study of the UV-protection LDH formulation was found to be biocompatible with HDF cells. 101 Hussein et al designed nanohybrid-based EA into ZnLHs and evaluated the cytotoxicity of the nanohybrid EA ZnLHs against the normal cell lines 3T3 and MCF-10A. The EA ZnLHs were found to be highly biocompatible with these normal cells, and at the same time EA ZnLHs were effective in killing two human cancer cell lines (breast cancer MCF-7 and liver cancer HepG2).…”
mentioning
confidence: 99%
“…The term "nanomedicine" is a new technology combining the use of both traditional medical technology and nanotechnology where nanosizeengineered materials of less than 100 nm size regime are employed. This interdisciplinary technology covers a wide range of therapeutic applications, from nanoparticulate drug delivery systems (e.g., carbon nanotubes, layered double hydroxides [7][8][9][10][11][12]), to in vitro (e.g., biosensor) and in vivo (e.g., imaging and implantable devices) diagnostics. The intentions of using nanomedicine in drug delivery applications are to achieve (1) improved delivery of water insoluble drugs [13]; (2) delivery of large macromolecule drugs to intracellular sites of action; (3) codelivery of two or more drugs or therapeutic agents for combination treatment; (4) transcytosis of drugs across tight epithelial and endothelial barriers [14]; (5) targeted delivery of drugs in a cell-or tissue-specific manner; (6) real-time read on the in vivo efficacy of a therapeutic agent, and (7) visualization of sites of drug delivery by combining therapeutic agents with imaging probes [15].…”
Section: Introductionmentioning
confidence: 99%
“…A new monophasic dualguest nanocomposite was obtained with slightly larger basal spacing from values reported for single-guest intercalation of B4 (21.3 Å) and EUS (21.0 Å). 22 We could attribute this to the interaction of larger molecular size of EUS with B4. We foresee bilayer arrangement by alternating chargebalancing SO 3…”
Section: θ °mentioning
confidence: 97%
“…Additionally, simulation under skin pH medium demonstrated low release of the intercalated UV ray absorbents over an extended period of time. 22 In the present work, we propose simultaneous intercalation of B4 and EUS into Zn/Al-LDH via coprecipitation method. The expected advantages of encapsulating organic UV ray absorbents within the interlayer region of LDHs are 1) increased photostability, 2) decreased release from formulation to skin, and 3) absence of direct contact with skin while maintaining UV ray absorption properties of anionic guest.…”
Section: -X M Iiimentioning
confidence: 99%